Upaya Meningkatkan Minat dan Kemampuan Mengaji bagi Anak Masyarakat Kute Ujung Barat melalui Pelaksanaan Program Tilawah Al Quran di TPA Al-Mukhsin - Sudirman Suparmin; Abdul Haris Kombih; Dia Ayu Khairani; Esi Ayu Audia; Eva Ayu Srirahmayani (MODELING: Jurnal Program Studi PGMI, 2023)
Recitation is one of the terms used in studying the science of the Qur'an. In general, recitations are known as a method of reading verses of the Qur'an with a tone or rhythm. This study aims to determine 1) the formulation of the Al-Qur'an recitation program in increasing students' interest and ability to read the Qur'an at TPA al-mukhsin Kute west end 2) the implementation of the Al-Qur'an recitation program in improving students' reading skills of the Qur'an at TPA al-Qur'an. mukhsin Kute west end. 3) evaluation of the Al-Qur'an recitation program in improving students' reading skills of the Qur'an at TPA al-Mukhsin Kute west end. This research is a qualitative research. Collecting research data using interviews, observation and documentation. The results of this study are: 1) the formulation of the recitation program was carried out at the Al-Mukhsin TPA Kute west end in mid-June which was supported by various parties, such as: the head of the AL-Mukhsin TPA, the deputy head of the Al-Mukhsin TPA, the Koran teacher, and KKN students. 02 UINSU, aims to help increase children's interest and ability to recite the Koran, the material provided is adjusted to the commemoration of Islamic holidays and other major celebrations. 2) the implementation of learning the Al-Qur'an recitation program is carried out on Mondays, Tuesdays and Wednesdays every 19:00 after maghrib prayers. 3) the process of evaluating the implementation of the Al-Qur'an recitation program at the al-Mukhsin Kute TPA west end is carried out once a week on Friday afternoon at 16:00 after Asr.